INNV-13. SYNERGISTIC EFFECT OF COLD ATMOSPHERIC PLASMA IN COMBINATION WITH TEMOZOLOMIDE TO TREAT GLIOBLASTOMA IN A NON-INVASIVE MOUSE XENOGRAFT MODEL. (9th November 2020) - Adhikari, Manish; Soni, Vikas; Hayk, Simonyan; Young, Colin; Sherman, Jonathan; Keidar, Michael
Abstract: INTRODUCTION: A primary limitation in anti-cancer therapy is the resistance of cancer cells to chemotherapeutic drugs. However, combination therapy may be an effective approach for reducing drug derived toxicity and evading drug resistance, resulting in improved clinical treatment of cancer. Our prior work demonstrated effective treatment of glioblastoma (GBM) with cold atmospheric plasma (CAP) technology with minimal effect to normal cells. Consequently, CAP may serve as a strong candidate for combination therapy with the classical antineoplastic alkylating agent Temozolomide (TMZ) to treat GBM. OBJECTIVES: To determine the in vivo co-efficacy of CAP and TMZ to "sensitize" GBM. METHODS: An in vivo study was performed using the CAP jet device (He-gas) to determine the effect of combined CAP–TMZ treatment. U87MG-luc glioblastoma cells were implanted intracranially in athymic nude NU(NCr)-Foxn1nu/immunodeficient mice. He-CAP (or control He alone) was non-invasively applied over the skin for 60sec to developed tumors on the first day of the treatment followed with 6.5 mg/kg TMZ or vehicle control treatment for 5 days for two weeks (n=5/group). In vivo bioluminescence imaging was used to monitor tumor volume on the 6 th, 9 th and 13 th treatment day. RESULTS: I n vivo bioluminescence imaging revealed a marked 8.0±3.2 fold increase in tumor volume in control animals (He-vehicle). Treatment with He-TMZ (6.7±2.5 fold) or CAP-vehicle (4.8±1.7 fold) in isolation had minimal effect in preventing tumor growth. However, combined CAP-TMZ co-treatment virtually prevented increases in tumor volume over 2 weeks (1.8±0.2 fold). CONCLUSIONS: Collectively, these findings indicate an effective synergistic treatment method for GBM combining CAP with TMZ. Future investigations look to incorporate radiation into the treatment regimen as well as primary GBM cell models.